PERFORMA AYAM BROILER YANG DIPELIHARA DENGAN PERBEDAAN KETINGGIAN KANDANG: PERFORMANCE OF BROILER CHICKENS MAINTAINED IN DIFFERENT CAGE HEIGHTS - Prasetyo, Hermawan; Wulandari, Eudia Christina; Prasetyo, Aris Budi (Tropical Animal Science, 2025)
This study aimed to evaluate the effect of cage floor height on broiler chicken performance in a closed house cage system. The parameters observed included feed consumption, body weight gain, Feed Conversion Ratio (FCR), performance index (IP), and mortality. The study used a Completely Randomized Design (CRD) with three treatments (0 m, 2 m, and 4 m floor) and six replications, where each replication consisted of 15 CP Charoen Phokpan strain broiler chickens. The results showed that cage height had a significant effect (P <0.05) on included feed consumption, body weight gain, Feed Conversion Ratio (FCR), performance index (IP), and mortality. A height of 4 m gave the best results with efficient feed consumption (49.92 g), the highest body weight gain (1.62 kg), the lowest FCR (1.65), the highest IP (292.23), and the lowest mortality (3%). Microenvironmental conditions such as temperature and humidity on the upper floor were more stable and supported the thermal comfort of the chickens, thus increasing growth efficiency. Thus, it can be concluded that the height of the cage is an important factor in the management of broiler chicken maintenance in the closed house system.